[I208] Annual quality assurance testing of radiological equipment: Why is this an important task of the MPE?. (August 2018) - Bosmans, Hilde
Abstract : Purpose: Often the role of the medical physicist in radiology is restricted to a quick annual test of the X-ray devices against set standards. Next to this, the medical physicist should perform many other tasks, such as optimization and justification. Aim of the lecture is to explain why Annual Quality Assurance testing of radiological equipment is an important task of the MPE: a complete series of tests next to a careful may point to the needs for system specific optimizations. This lecture selects material from the EUTEMPE-RX, module 6, devoted to improved Quality Assurance (for new equipment or when standards are insufficient to guarantee good practice). Methods: Discuss the difference between testing the 'acceptability' of radiological devices and verification of the complete imaging chain. Illustrate how the annual QA test can be used to learn about the equipment and its use, to measure the (application specific) system performance and to launch optimization processes. Results: Better awareness of what can be done by the MPE at the occasion of the annual QA test should lead to better annual test protocols that will help guarantee the optimized use of radiation. Conclusions: It is important to perform relevant tests, to focus on the radiological tasks performed with a device and test accordingly, to verify the complete imaging chain (up to the visualization of the digital image), to compare to peers and to communicate with the imaging team at several occasions.